Porous membrane, filter member, and member supply assembly
By using a porous membrane made of thermoplastic resin with a melting point above 180℃ and below 300℃, combined with a tortoise shell-like structure and a low compressibility design, the problem of insufficient mechanical strength of the porous membrane during device installation is solved, and a stable installation effect is achieved.
Patent Information
- Application Number
- CN202480037775.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-09
- Filing Date
- 2024-06-07
- Publication Date
- 2026-01-02
AI Technical Summary
Existing porous membranes have difficulty ensuring suitable installation pressure during device mounting, especially due to insufficient mechanical strength during installation processes such as housing mounting.
The main component is a thermoplastic resin with a melting point of 180℃ or higher and 300℃ or lower. A porous membrane with a tortoise shell-like structure composed of multiple nodes and multiple protofibrils is formed. When a pressure of 2.5 N/mm2 is applied in the thickness direction, the compression rate is less than 20%. An adhesive layer is combined to achieve stable installation.
The design, featuring a tortoise-shell structure and low compressibility, ensures that the porous membrane is not easily compressed during installation, allowing for stable installation on housings and other surfaces, and providing suitable installation pressure.
Smart Images

Figure CN121263471A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a porous membrane, a filter member, and a member supply assembly. BACKGROUND
[0002] Porous membranes of fluororesins are used for various applications such as filters, sound permeable membranes, air permeable membranes, diaphragms, liquid absorbers, and the like. In order to be used for these applications, porous membranes not containing fluorine have also been proposed.
[0003] For example, Patent Literature 1 discloses an olefin-based resin microporous biaxially stretched film characterized by having a microporous portion and containing an olefin-based resin, a puncture strength of 0.7 N or more, and an air permeability of 75 to 400 s / 100 mL.
[0004] PRIOR ART DOCUMENTS
[0005] PATENT LITERATURE
[0006] Patent Literature 1: Japanese Patent Application Publication No. 2017-095576 SUMMARY
[0007] PROBLEMS TO BE SOLVED BY THE INVENTION
[0008] Even a porous membrane excellent in mechanical strength such as puncture strength, for example, sometimes cannot ensure a suitable mounting pressure at the time of mounting of a device to a case or the like.
[0009] Therefore, an object of the present application is to provide a porous membrane suitable for mounting of a device to a case or the like.
[0010] SOLUTION TO PROBLEM
[0011] The present application provides a porous membrane comprising, as a main component, a thermoplastic resin having a melting point of 180°C or higher and 300°C or lower,
[0012] The porous membrane has a tortoise shell-like structure formed of a plurality of nodes and a plurality of fibrils.
[0013] Viewed from another aspect, the present application provides a porous membrane comprising, as a main component, a thermoplastic resin having a melting point of 180°C or higher and 300°C or lower,
[0014] The compression rate in the thickness direction of the porous membrane when a pressure of 2.5 N / mm 2 is applied is 20% or less.
[0015] In addition, viewed from another aspect, the present application provides a filter member comprising:
[0016] the above-described porous membrane of the present application; and
[0017] an adhesive layer joined to the porous membrane.
[0018] Furthermore, from another perspective, the present invention provides a component supply assembly comprising: a filter component disposed on the surface of an object having an open face; and a substrate sheet on which the filter component is disposed.
[0019] The filter component includes:
[0020] A porous membrane having a shape that covers the opening when disposed on the surface; and
[0021] An adhesive layer bonded to the porous membrane,
[0022] The porous membrane is the porous membrane of the present invention described above.
[0023] The effects of the invention
[0024] According to the present invention, it is possible to provide a porous membrane suitable for mounting devices in housings, etc. Attached Figure Description
[0025] Figure 1A This is a cross-sectional view schematically illustrating an example of the porous membrane of the present invention.
[0026] Figure 1B This is a schematic diagram illustrating an example of the surface of the porous membrane of the present invention.
[0027] Figure 2 This is a cross-sectional view schematically illustrating an example of the breathable component of the present invention.
[0028] Figure 3 It is shown schematically. Figure 2 A cross-sectional view of a modified example 1 of a breathable component.
[0029] Figure 4 It is shown schematically. Figure 2 A cross-sectional view of a modified example 2 (wound body) of a breathable component.
[0030] Figure 5 This is a cross-sectional view schematically illustrating an example of a filter component of the present invention.
[0031] Figure 6 It is shown schematically. Figure 5 A cross-sectional view of a modified example 1 of filter component 4.
[0032] Figure 7 It is shown schematically. Figure 5 A cross-sectional view of a modified example 2 of filter component 4.
[0033] Figure 8 It is shown schematically. Figure 5 A cross-sectional view of a modified example 3 of the filter component 4.
[0034] Figure 9 is a sectional view schematically showing an example of the member supply assembly of the present application.
[0035] Figure 10 is a graph showing the result of observing the surface of the porous membrane of Example 1 with a scanning electron microscope (SEM) (2500x).
[0036] Figure 11 is a graph showing the result of observing the surface of the porous membrane of Example 2 with a SEM (2500x).
[0037] Figure 12A is a graph showing the result of observing the surface of the porous membrane of Example 3 with a SEM (2500x).
[0038] Figure 12B is a partial enlarged view (10000x) of Figure 12A .
[0039] Figure 12C is a graph showing the result of observing the cross section of the porous membrane of Example 3 with a SEM (1500x).
[0040] Figure 13 is a graph showing the result of observing the surface of the porous membrane of Example 4 with a SEM (2500x).
[0041] Figure 14A is a graph showing the result of observing the surface of the porous membrane of Example 5 with a SEM (2500x).
[0042] Figure 14B is a partial enlarged view (10000x) of Figure 14A .
[0043] Figure 15A is a graph showing the result of observing the surface of the membrane of Comparative Example 1 with a SEM (2500x).
[0044] Figure 15B is a partial enlarged view (10000x) of Figure 15A .
[0045] Figure 15C is a graph showing the result of observing the cross section of the membrane of Comparative Example 1 with a SEM (2000x).
[0046] Figure 16 is a graph showing the result of observing the surface of the membrane of Comparative Example 2 with a SEM (2500x).
[0047] Figure 17 is a graph showing the result of observing the surface of the membrane of Comparative Example 3 with a SEM (2500x).
[0048] Figure 18A is a photograph (2500 times) showing the result of observing the surface of the film of Reference Example 2 with an SEM.
[0049] Figure 18B is a partial enlarged view (20000 times) of Figure 18A .
[0050] Figure 19 is a graph showing the result of measuring the actual temperature of the film from after heat-pressing until cooling with a thermocouple at intervals of 100 ms for Example 1, Examples 6 to 7, and Comparative Example 4.
[0051] Figure 20 is a schematic diagram for explaining the method of finding the distance between island-like regions of the porous film of Fig. 1.
[0052] Figure 21 is a schematic sectional view for explaining the compression test. DETAILED DESCRIPTION
[0053] The porous film of the first aspect of the present application contains a thermoplastic resin having a melting point of 180°C or higher and 300°C or lower as a main component,
[0054] The porous film has a tortoise-shell-like structure formed of a plurality of nodes and a plurality of fibrils.
[0055] In the second aspect of the present application, for example, in the porous film of the first aspect, the compression rate in the thickness direction of the porous film when a pressure of 2.5 N / mm 2 is applied is 20% or lower.
[0056] The porous film of the third aspect of the present application contains a thermoplastic resin having a melting point of 180°C or higher and 300°C or lower as a main component,
[0057] The compression rate in the thickness direction of the porous film when a pressure of 2.5 N / mm 2 is applied is 20% or lower.
[0058] In the fourth aspect of the present application, for example, in the porous film of any one of the first to third aspects, the thermoplastic resin contains a polymethylpentene resin.
[0059] In the fifth aspect of the present application, for example, in the porous film of any one of the first to fourth aspects, a plurality of the nodes are contained along the thickness direction when a cross section of the porous film is observed.
[0060] In the sixth aspect of the present application, for example, in the porous film of any one of the first to fifth aspects, the air permeability is 1000 seconds / 100 mL or lower in terms of Gurley number.
[0061] In the seventh aspect of the present invention, for example, in the porous membrane of any one of the first to sixth aspects, the porosity of the porous membrane is 25% or more.
[0062] The filter component of the eighth embodiment of the present invention comprises:
[0063] The porous membrane described in any one of the first to seventh methods; and
[0064] An adhesive layer bonded to the porous membrane.
[0065] The ninth aspect of the present invention provides a component supply assembly comprising: a filter component disposed on the surface of an object having an opening; and a substrate sheet on which the filter component is disposed.
[0066] The filter component includes:
[0067] A porous membrane having a shape that covers the opening when disposed on the surface; and
[0068] An adhesive layer bonded to the porous membrane,
[0069] The porous membrane is any one of the first to seventh methods.
[0070] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. The present invention is not limited to the following embodiments.
[0071] [Porous membrane]
[0072] An example of the porous membrane of the present invention is shown in Figure 1A . Figure 1A The porous membrane 1 contains a thermoplastic resin with a melting point of 180°C or higher and 300°C or lower as its main component. "Main component" refers to the component with the highest content by weight in the porous membrane. With this configuration, the porous membrane 1 can be used, for example, not limited to the use of an adhesive layer, and can also be bonded to a housing or the like via thermal fusion.
[0073] Figure 1B This is a schematic diagram illustrating an example of the surface of a porous membrane 1. The porous membrane 1 has a tortoise-shell-like structure formed by multiple nodes 1a and multiple fibrils 1b. Figure 1B As shown, a tortoise-shell-like structure exists throughout the porous membrane 1. This structure suppresses the reduction in thickness of the porous membrane 1 caused by compression during mounting of the device to a housing or similar object. Therefore, suitable mounting pressure can be ensured. The tortoise-shell-like structure can be observed, for example, by viewing the main surface of the porous membrane 1 from a vertical direction. In this invention, "main surface" refers to the surface with the largest area of a sheet-like or thin-film component. Furthermore, in this disclosure, "main surface" and "surface" of the porous membrane 1 are used interchangeably.
[0074] In the present application, the "scaly structure formed of the plurality of nodes 1a and the plurality of fibrils 1b" is a structure that can be confirmed by performing scanning electron microscope (SEM) observation on the surface of the porous membrane 1, and refers to a structure in which the island-shaped regions 1c formed of the plurality of nodes 1a are irregularly connected and these island-shaped regions 1c are connected to each other by the plurality of fibrils 1b. As the island-shaped region 1c, for example, a polygonal region can be cited. Note that the outline of the polygonal region is not necessarily composed of only straight lines, and a substantially polygonal region in which a part of the sides is a curved line such as a circular arc is also included. The polygon is, for example, a hexagon, but is not limited thereto, and can be, for example, a pentagon, or a quadrangle. The scaly structure can include a plurality of island-shaped regions 1c and a plurality of fibrils 1b each extending in a plurality of directions from the island-shaped regions 1c. The island-shaped regions 1c can also be connected to or coincide with each other without the plurality of fibrils 1b (see Section I of Figure 1B ). That is, the plurality of fibrils 1b can not exist between the adjacent island-shaped regions 1c. The island-shaped regions 1c and the nodes 1a as the aggregate of the plurality of nodes 1a can also be mixed (see Section II of Figure 1B ). A planar region 1d formed by the plurality of fibrils 1b densely extending in a plurality of directions from each of the island-shaped regions 1c can also exist (see Section III of Figure 1B ). When the surface of the porous membrane 1 is observed by SEM, the planar region 1d formed by the plurality of fibrils 1b densely extending can sometimes be indistinct at first glance from the island-shaped region 1c formed of the plurality of nodes 1a. However, even in such a case, for example, by enlarging the observed image to about 10,000 times, the island-shaped region 1c and the planar region 1d can be distinguished. The island-shaped region 1c can also have a shape that is more raised than the planar region 1d. When the surface of the porous membrane 1 is observed by SEM, the longest diameter of the island-shaped region 1c can be 0.5 μm or more, 1 μm or more, and further 2 μm or more.
[0075] Note that in the present disclosure, "scaly" is a term focusing on the island-shaped region 1c, and indicates a pattern in which the island-shaped regions 1c are irregularly arranged like the carapace of a tortoise, and does not mean that the island-shaped regions 1c are necessarily densely arranged like the carapace of a tortoise.
[0076] The average interval between the adjacent island-shaped regions 1c and the island-shaped regions 1c is, for example, 0.1 μm or more and 30 μm or less. The lower limit of the average interval of the island-shaped regions 1c can be 0.5 μm or more, can be 1 μm or more, can be 2 μm or more, and further can be 4 μm or more. The upper limit of the average interval of the island-shaped regions 1c can be 20 μm or less, can be 15 μm or less, can be 10 μm or less, and further can be 8 μm or less.
[0077] The average area of the island-shaped region 1c is, for example, 0.1 μm 2 or more, and 100 μm or less 2 The lower limit of the average area of the island-shaped region 1c can be 0.5 μm 2 or more, and 1 μm or less 2 or more, and 5 μm or less 2 or more, and 10 μm or less 2 or more, and further 14 μm or less 2 The upper limit of the average area of the island-shaped region 1c can be 75 μm 2 or more, and 65 μm or less 2 or more, and 55 μm or less 2 or more, and further 50 μm or less 2 or less.
[0078] The average interval between the island-shaped regions of the porous membrane 1 can be obtained by the method described below. Figure 20 is a schematic diagram for explaining Figure 1A the method of obtaining the distance between the island-shaped regions of the porous membrane 1. First, the surface of the porous membrane 1 is observed with an SEM (for example, refer to Figure 1B ). Next, the obtained SEM observation image (or a part thereof) is subjected to a binaryzation process using an image analysis software. The island-shaped regions are recognized from the obtained binaryzation image, and the area of each island-shaped region contained in the image is calculated. For each island-shaped region, the equivalent circle diameter is calculated from the calculated area. The equivalent circle diameter refers to the diameter of a true circle having the same area as the area of the island-shaped region that is the object of measurement. As shown in Figure 20 , the distance L AB between the island-shaped regions of the island-shaped region A and the island-shaped region B can be obtained as a value obtained by subtracting the equivalent circle diameter of the island-shaped region A x 1 / 2 and the equivalent circle diameter of the island-shaped region B x 1 / 2 from the distance between the center of gravity c of the island-shaped region A and the center of gravity c of the island-shaped region B. In this way, for the three island-shaped regions (the island-shaped region B, the island-shaped region C, and the island-shaped region D) having the first nearest to the third nearest distance from the island-shaped region A, the distances between the island-shaped regions (L AB , L AC , and L AD ) are obtained. That is, the distance between the island-shaped regions (L AE). However, an island region (island region F) overlapping with the island region A in the image is excluded from the three island regions at the first to third proximities from the island region A. The average of the distances between the island regions thus calculated with the three island regions proximate to the island region A is regarded as the distance between the island regions of the island region A. The distance between the island regions is similarly calculated for each of the island regions included in the image. The average of the distances between the island regions thus calculated can be regarded as the average interval between the island regions of the porous membrane 1. Note that, in identifying the island regions, the island regions at the ends of the image are omitted from the analysis. As the image analysis software, for example, imageJ can be used.
[0079] The average area of the island regions of the porous membrane 1 can be calculated by the following method. First, a binary image is obtained by the same method as that described for the calculation of the distance between the island regions of the porous membrane 1, and the nodes are identified from the binary image. The island regions are identified from the binary image thus obtained, and the area of each of the island regions included in the image is calculated. The average of the areas of the island regions thus calculated can be regarded as the average area of the island regions of the porous membrane 1. Note that the average area of the island regions of the porous membrane 1 is determined by measuring 30 or more, for example, 50 to 200 island regions.
[0080] Figures 10-12B Figures 13-14B are graphs showing the results of observation of the surfaces of the porous membranes of Examples 1 to 5 with SEM. As shown in these observation images, the surfaces of the porous membranes of Examples 1 to 5 have a tortoise-shell-like structure formed of a plurality of nodes and a plurality of fibrils. Specifically, the island regions 1c formed of a plurality of nodes 1a are irregularly connected, and these island regions 1c are connected to each other by a plurality of fibrils 1b.
[0081] When the cross section of the porous membrane 1 is observed, a plurality of nodes can be included along the thickness direction. The plurality of nodes can exist throughout the thickness direction of the porous membrane 1. By such a structure, reduction in the film thickness caused by compression at the time of mounting of the device to a housing or the like can be suppressed.
[0082] The nodes existing in the thickness direction can also be block-shaped. That is, when the cross section of the porous membrane 1 is observed, a plurality of block-shaped nodes can be included along the thickness direction. The block-shaped nodes existing in the thickness direction correspond to the island regions when the surface of the porous membrane 1 is observed with SEM.
[0083] The plurality of block-shaped nodes can exist uniformly throughout the thickness direction of the porous membrane 1. The adjacent block-shaped nodes can be connected by a plurality of fibrils, and the adjacent block-shaped nodes can also not be connected by a plurality of fibrils but the block-shaped nodes can be directly connected to each other.
[0084] Figure 12C is a graph showing the result of observing the cross section of the porous film of Example 3 with an SEM. As shown in Figure 12C , when the cross section of the porous film of Example 3 was observed, a plurality of block-like nodes were contained along the thickness direction. The plurality of block-like nodes were present throughout the entire thickness direction of the porous film.
[0085] The compression ratio Rc of the porous film 1 in the thickness direction of the porous film 1 at the time of applying a pressure of 2.5 N / mm 2 was 20% or less. The compression ratio Rc is a value per unit amount of resin. Thus, in the porous film 1, reduction in film thickness due to compression at the time of mounting of a device to a housing or the like was suppressed, and thus a suitable mounting pressure can be ensured.
[0086] The compression ratio Rc can be found by a compression test using a thermomechanical measuring device (TMA). Figure 21 is a schematic cross-sectional view for explaining the compression test. First, the porous film 1 was cut into a long strip shape of width 10 mm x length 10 mm, as a sample piece S. Next, in an environment of 25°C, a load was gradually applied from an initial load Pl (gf) (refer to (A) of Figure 21 ) to a maximum load P max (gf) (refer to (B) of Figure 21 ) using a cylinder-shaped indenter 90 of the TMA with a tip diameter of 1 mm, and the sample piece S was compressed at a load speed of 50 gf / minute, while a function Fl of the load P n (gf) and the deformation rate (%) in the compression direction was obtained. Note that the deformation rate (%) under the load P n (gf) is the thickness T n (μm) of the sample piece S under the load P n (gf) relative to the thickness Tl (μm) of the sample piece S under the initial load Pl (gf), and is found by 100 x T n / Tl. Next, using the area (0.785 mm 2 ) of the indenter 90, the function Fl was converted into a function F2 of the load Pa (gf / mm 2 ) per unit area and the deformation rate (%) (load Pa (gf / mm 2 ) = load P n (gf) / 102 / area of the indenter 90 (mm 2 ). Further, the function F2 was converted into a function F3 of the deformation rate (%) under the load Pb (gf / mm 2 ) per unit amount of resin, taking into account the pores present in the porous film 1 (load Pb (gf / mm 2 ) = load Pa (gf / mm 2) / (100 - porosity) / 100). In the function F3, the load Pb is 2.5 gf / mm 2 The deformation rate (%) at the time of 2.5 gf / mm 2.5 The value calculated by 100 - R 2.5 is regarded as the compression rate Rc (%). The measurement conditions of the above compression test are shown below.
[0087] <Measurement Conditions>
[0088] Initial load P1: 2 gf
[0089] Maximum load P max : 500 gf
[0090] Load speed: 50 gf / minute
[0091] The compression rate Rc can be 19.5% or less, or 19% or less. The lower limit of the compression rate Rc is, for example, 5%.
[0092] As described above, the melting point of the thermoplastic resin included in the porous membrane 1 is 180°C or higher and 300°C or lower. By making the melting point of the thermoplastic resin 180°C or higher, sufficient heat resistance can be ensured in the porous membrane 1. By making the melting point of the thermoplastic resin 300°C or lower, the porous membrane 1 can be produced, for example, by melt molding.
[0093] The melting point of the thermoplastic resin can be 200°C or higher and 280°C or lower, or further 220°C or higher and 260°C or lower.
[0094] The thermoplastic resin having a melting point of 180°C or higher and 300°C or lower can be a thermoplastic resin not containing fluorine. The thermoplastic resin not containing fluorine can be a polyolefin resin. The polyolefin resin includes a polyethylene (PE) resin, a polypropylene (PP) resin, and a polymethylpentene (PMP) resin.
[0095] As the thermoplastic resin, for example, a poly(4-methylpentene-1) resin (polymethylpentene resin), a poly(3-methylbutene-1) resin, and the like can be listed. Examples of the poly(4-methylpentene-1) resin include a polymethylpentene resin having a melting point of 180°C or higher and 300°C or lower. Examples of the poly(3-methylbutene-1) resin include a polymethylbutene resin having a melting point of 180°C or higher and 300°C or lower. Examples of the poly(4-methylpentene-1) resin and the poly(3-methylbutene-1) resin include a polymethylpentene resin having a melting point of 200°C or higher and 280°C or lower, or further 220°C or higher and 260°C or lower. Examples of the poly(4-methylpentene-1) resin and the poly(3-methylbutene-1) resin include a polymethylpentene resin having a melting point of 180°C or higher and 300°C or lower, and a polymethylpentene resin having a melting point of 200°C or higher and 280°C or lower, or further 220°C or higher and 260°C or lower.
[0096] The thermoplastic resin can also be a polymethylpentene resin. The polymethylpentene resin is a homopolymer or a copolymer of a poly(4-methylpentene-1) resin, a poly(3-methylpentene-1) resin, or the like. As the copolymer, there are a random copolymer, a block copolymer, and the like. From the aspects of heat resistance and molding processability, a homopolymer of the poly(4-methylpentene-1) resin is preferable. The polymethylpentene resin has a melting point of 230°C to 240°C. Thus, according to such a configuration, a porous membrane that is suitable for suppressing a decrease in thickness caused by compression at the time of mounting a device to a case or the like is easily obtained.
[0097] The thermoplastic resin can be a poly(4-methylpentene-1) resin. The poly(4-methylpentene-1) resin refers to a homopolymer of 4-methylpentene-1, or a copolymer of 4-methylpentene-1 and at least one α-olefin. The composition ratio of 4-methylpentene-1 to the α-olefin included in the copolymer can be adjusted within a range in which the melting point is 180°C or higher.
[0098] The porous membrane 1 can contain, in addition to the thermoplastic resin, an additive such as a plasticizer, an antioxidant, or the like.
[0099] The air permeability of the porous membrane 1 in the thickness direction can be 0.1 / 100 mL or more and 10,000 seconds / 100 mL or less, in Gurley number. In the present specification, the "Gurley number" is the air permeability resistance (Gurley air permeability) measured in accordance with the Gurley method prescribed in JIS P8117:2009. The lower limit of the air permeability of the porous membrane 1 can be 10 seconds / 100 mL or more, 30 seconds / 100 mL or more, 50 seconds / 100 mL or more, or further 70 seconds / 100 mL or more, in Gurley number. The upper limit of the air permeability of the porous membrane 1 can be 5,000 seconds / 100 mL or less, 1,000 seconds / 100 mL or less, or further 500 seconds / 100 mL or less, in Gurley number.
[0100] Note that, in the case where the size of the porous membrane 1 does not satisfy the recommended size (50 mm x 50 mm) of the test piece of the Gurley method, evaluation of the air permeability resistance (Gurley air permeability) based on the Gurley method can also be performed by using a measuring jig.
[0101] The measuring fixture has a shape and size suitable for mounting the air permeability measuring section of a pressure testing machine, and is made of a thickness and material that will not deform due to pressure differential applied to the test piece when measuring air permeability resistance. An example of the measuring fixture is a SUS circular plate with a thickness of 2 mm and a diameter of 47 mm. A through-hole with an opening smaller than the size of the membrane being evaluated is pre-formed at the center of the surface of the measuring fixture. The cross-section of the through-hole is typically circular, and is set to the diameter of the opening of the through-hole completely covered by the membrane being evaluated. For example, 1 mm or 2 mm can be used as the diameter of the through-hole. Next, the porous membrane 1 being evaluated is fixed to one surface of the measuring fixture in a manner that covers the opening. The fixing is performed in such a way that, during the measurement of air permeability resistance, air passes only through the opening and the effective test section of the porous membrane 1 being evaluated (the portion overlapping the opening when viewed from a direction perpendicular to the main surface of the fixed porous membrane 1), and the fixed portion does not obstruct the passage of air through the effective test section of the porous membrane 1. In fixing the porous membrane 1, a double-sided adhesive tape with a vent hole of the same shape as the opening punched in the center can be used. The double-sided adhesive tape is positioned between the measuring fixture and the porous membrane 1 such that the periphery of the vent hole matches the periphery of the opening. Next, the measuring fixture with the porous membrane 1 fixed is placed in the air permeability measuring section of the Wang Yan type testing machine with the fixed surface of the porous membrane 1 facing downstream of the airflow during measurement. A test based on the Wang Yan type testing machine method is performed, and the air permeability resistance indication value t shown by the testing machine is recorded. Then, the result is obtained using formula t. K ={t×(area of the effective test section of porous membrane 1 [cm²])} 2 ]) / 6.452[cm 2 The recorded air permeability resistance indicator value t is converted into the 6.452 cm values specified in the Wang Yan-style testing machine method. 2 The effective test area value t K The obtained conversion value t K The air permeability resistance (Grey air permeability) of the porous membrane 1 was measured according to the Wang Yan-style testing machine method. It should be noted that the air permeability resistance measured without the use of a measuring fixture for the porous membrane 1 with the recommended test piece size (50mm×50mm) that meets the Wang Yan-style testing machine method was confirmed to be highly consistent with the air permeability resistance measured with a measuring fixture after the porous membrane 1 was sliced into smaller pieces. That is, the use of the measuring fixture does not substantially affect the measured value of the air permeability resistance.
[0102] The water pressure resistance of the porous membrane 1 is evaluated by the water resistance test method B (high water pressure method) specified in JIS L1092:2009, and can be above 10 kPa. The lower limit of the water pressure resistance of the porous membrane 1 can be above 100 kPa, above 130 kPa, or even above 150 kPa. The upper limit of the water pressure resistance of the porous membrane 1 is, for example, below 2000 kPa.
[0103] The water pressure resistance of the porous film 1 can be measured using a measuring jig according to the above water resistance test method as follows. One example of the measuring jig is a circular plate made of stainless steel (SUS) having a diameter of 47 mm with a through hole (having a circular cross section) of 2.0 mm in diameter provided in the center. The circular plate has a thickness that does not deform due to the water pressure applied when measuring the water pressure resistance. The measurement of the water pressure resistance using this measuring jig can be performed as follows.
[0104] The porous film 1 serving as the evaluation object is fixed to one face of the measuring jig in a manner so as to cover the opening of the through hole of the measuring jig. Regarding the fixing, in the fixing of the porous film 1 in the measurement of the water pressure resistance in a manner so that water does not leak from the fixed portion of the film, a double-sided adhesive tape having a water passage punched in the center portion having a shape in accordance with the shape of the opening can be used. The double-sided adhesive tape can be disposed between the measuring jig and the porous film 1 in a manner so that the periphery of the water passage coincides with the periphery of the opening. Next, the measuring jig on which the porous film 1 is fixed is disposed in the test device in a manner so that the face of the porous film 1 opposite to the fixed face becomes the water pressure application face at the time of measurement, and the water pressure resistance is measured according to the water resistance test B method (high water pressure method) prescribed in JIS L1092:2009. Here, the water pressure resistance is measured based on the water pressure at the time when water flows out from one place of the film face of the porous film 1. The measured water pressure resistance can be taken as the water pressure resistance of the porous film 1. The test device can use a device having the same configuration as the water resistance test device exemplified in JIS L1092:2009 and having a test piece mounting structure capable of disposing the above measuring jig.
[0105] The porosity of the porous film 1 is, for example, 25% or more. The porosity of the porous film 1 can be 20% or more or 35% or more. The porosity can be calculated by substituting the mass, the thickness, the area (area of the main surface), and the true density of the porous film 1 into the following formula (1).
[0106] Porosity (%) = {1 - (mass [g] / (thickness [cm] x area [cm 2 ] x true density [g / cm 3 ])} x 100 Formula (1)
[0107] The upper limit of the porosity of the porous film 1 is, for example, 95%. The upper limit of the porosity of the porous film 1 can be 90%.
[0108] The porous film 1 can be in a sheet shape or a film shape. The thickness of the porous film 1 is, for example, 1 μm or more and 100 μm or less. By being such a structure, reduction in the film thickness due to compression at the time of mounting of a device to a housing or the like is easily suppressed. The thickness of the porous film 1 can be 5 μm or more and 80 μm or less or 10 μm or more and 70 μm or less.
[0109] The thickness of the porous film 1 can be measured, for example, at five points of the porous film 1 using a micrometer, and the average of these measured values can be taken as the thickness of the porous film 1. The thickness of the porous film 1 can also be measured at five points of a cross-sectional SEM observation image of the porous film 1, and the average of these measured values can be taken as the thickness of the porous film 1.
[0110] At least one main surface of the porous film 1 can be subjected to a surface modification treatment. As the surface modification treatment, for example, a chemical treatment, a sputter etching treatment, a liquid repellent treatment, a plasma treatment, or the like can be cited. In a region subjected to the surface modification treatment, the bonding property of the porous film 1 is improved.
[0111] [Method for manufacturing porous film]
[0112] The porous film 1 described above can be manufactured, for example, by the following method.
[0113] The method for manufacturing the porous film 1 includes: kneading a composition containing a thermoplastic resin having a melting point of 180°C or higher and 300°C or lower and a plasticizer to obtain a kneaded product (step S1); subjecting the kneaded product to hot pressing to obtain a pressed body (step S2); cooling the pressed body to obtain a molded body (step S3); stretching the molded body to obtain a sheet body (step S4); and extracting the plasticizer from the sheet body (step S5).
[0114] Steps S1 to S3 correspond to a process of producing a precursor of the porous film 1. Steps S4 to S5 correspond to a process of growing a porous structure.
[0115] Step S1 is performed, for example, at a temperature of 230°C to 260°C for 5 minutes to 30 minutes.
[0116] As the thermoplastic resin having a melting point of 180°C or higher and 300°C or lower, a polymethylpentene resin can be used.
[0117] In the composition containing the thermoplastic resin and the plasticizer, a resin such as polyethylene, polypropylene, poly-1-butene, a cyclic polyolefin, or the like can be mixed within a range that does not affect the properties of the porous film 1.
[0118] The plasticizer is a non-volatile solvent that forms a mixture above the melting point of the thermoplastic resin such as a polymethylpentene resin when mixed with the resin, and exhibits thermotropic phase separation when the mixture is cooled. The plasticizer can be a liquid at normal temperature, or can be a solid. The plasticizer can be used alone, or two or more plasticizers can be mixed and used. As such a plasticizer, for example, a plasticizer having a kinematic viscosity of 50 to 150 mm 2 / s at 40°C can be used.
[0119] The mixing ratio of the thermoplastic resin and the plasticizer is set in a manner that enables obtaining a uniform mixture in step S1 and enables forming a molded body in step S3. Specifically, the weight ratio of the thermoplastic resin in the composition containing the thermoplastic resin and the plasticizer is, for example, 20% by weight or more and 80% by weight or less, and preferably 30% by weight or more and 70% by weight or less. By making the weight ratio of the thermoplastic resin 20% by weight or more, it is possible to avoid excessive reduction in the viscosity of the composition. By making the weight ratio of the thermoplastic resin 80% by weight or less, it is easy to obtain a good porous structure.
[0120] In the composition containing the thermoplastic resin and the plasticizer, an antioxidant, a crystallization nucleating agent, an antistatic agent, a flame retardant, a lubricant, an ultraviolet absorber, a coloring agent, an inorganic filler for improving strength, and the like can be further mixed as an additive according to the purpose.
[0121] Step S2 is performed, for example, at a temperature of 230°C to 260°C for a time of 2 minutes to 30 minutes. The thickness of the press-molded body obtained by step S2 is, for example, 0.1 mm.
[0122] In step S3, for example, the press-molded body obtained by step S2 is brought into contact with a heat transfer body to be cooled to a temperature sufficiently lower than the crystallization temperature of the thermoplastic resin and solidified. As the heat transfer body for cooling, for example, water, air, a plasticizer, a metal, and the like can be listed. The heat transfer body for cooling is preferably water.
[0123] In step S4, the molded body is subjected to stretching in at least a uniaxial direction at least once. The stretching in the at least uniaxial direction includes uniaxial stretching in the longitudinal direction, uniaxial stretching in the transverse direction, simultaneous biaxial stretching, and sequential biaxial stretching. The biaxial stretching can be performed on the molded body sequentially, or the biaxial stretching can be performed on the molded body simultaneously. By step S4, pores are generated in the molded body.
[0124] The stretching temperature can be 20°C to 240°C, 50°C to 230°C, or 100°C to 220°C in the longitudinal stretching and the transverse stretching, respectively.
[0125] The stretching ratio can be 2.0 times to 10.0 times, 2.0 times to 8.0 times, or 2.0 times to 5.0 times in the uniaxial direction of the longitudinal direction and / or the transverse direction.
[0126] The strain rate in the stretching can be 1% / second to 10% / second, 2% / second to 8% / second, or 3% / second to 5% / second in the longitudinal direction and / or the transverse direction. When the strain rate is in the above numerical range, it is less likely to occur breakage during the stretching, and the productivity is further improved. By making the strain rate in the above numerical range, it is easy to apply 2.5 N / mm 2Porous membranes with a thickness-direction compressibility Rc of less than 20% under pressure.
[0127] In step S5, for example, an extraction solvent is used to extract and remove the plasticizer from the sheet.
[0128] As the extraction solvent, a solvent that is a poor solvent relative to thermoplastic resins such as polymethylpentene resin, but a good solvent relative to plasticizers, and whose boiling point is lower than the melting point of the porous membrane is preferred. Examples of such extraction solvents include hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as dichloromethane and 1,1,1-trichloroethane; alcohols such as ethanol and isopropanol; ethers such as diethyl ether and tetrahydrofuran; and ketones such as acetone and 2-butanone. Alcohols and ketones are preferred when considering safety, etc. Methyl ethyl ketone (MEK) can be used as an extraction solvent.
[0129] Between steps S4 and S5, heat curing can also be performed on the sheet. Heat curing can be performed, for example, using a hot air circulating oven. By performing heat curing, the thermal shrinkage of the stretched sheet can be reduced. The heat curing temperature is, for example, 50°C to 240°C. The heat curing temperature can be 100°C to 230°C, and more specifically, 150°C to 220°C.
[0130] Heat setting can also be performed in two stages: after step S4, between steps S4 and S5, or after steps S4 and S5. Examples of heat setting methods include using a tenter frame to fix the width direction and continuously pass the material through the heat treatment furnace, applying appropriate tension to continuously pass the material through the heat treatment furnace without fixing the width direction, or winding the material onto a roller and feeding it into the heat treatment furnace in batches.
[0131] [Breathable components]
[0132] An example of the breathable component of the present invention is shown in Figure 2 . Figure 2 The breathable component 2 (2A) has a porous membrane 1. Figure 3 Show Figure 2 Example 1: Deformation of the breathable component. Figure 3 The breathable component 2 (2B) also includes a breathable support material 3. The breathable support material 3 is laminated on the porous membrane 1. The breathable support material 3 improves the strength and operability of the breathable component 2.
[0133] The air-permeable support material 3 generally has high air permeability in the thickness direction compared with the porous film 1. Examples of the air-permeable support material 3 are woven cloth, nonwoven cloth, net, and mesh. Examples of the material constituting the air-permeable support material 3 are polyester such as polyethylene terephthalate (PET), polyolefin such as polyethylene (PE) and polypropylene (PP), and aramid resin. The shape of the air-permeable support material 3 when viewed perpendicularly to the main surface of the air-permeable member 2 can be the same as or different from the shape of the porous film 1. The air-permeable support material 3 can have a shape corresponding to the peripheral edge portion of the porous film 1 when viewed perpendicularly to the main surface of the air-permeable member 2. The shape is annular in the case where the shape of the porous film 1 is circular. The constitution and shape of the air-permeable support material 3 are not limited to the above examples.
[0134] Figure 3 The air-permeable member 2B of the present embodiment has one air-permeable support material 3 disposed on one face of the porous film 1. The air-permeable member 2 can have two or more air-permeable support materials 3. In the air-permeable member 2, the air-permeable support material 3 can be disposed on both faces of the porous film 1. The porous film 1 and the air-permeable support material 3 can be joined by fusion such as heat fusion and ultrasonic fusion, an adhesive or a bonding agent.
[0135] The air-permeable member 2 can have any layer and / or member other than the above.
[0136] The thickness of the air-permeable member 2 is, for example, 1 to 300 μm, and can be 50 to 200 μm.
[0137] The weight per unit area of the air-permeable member 2 is, for example, 1.0 to 200.0 g / m 2 , and can be 10.0 to 100.0 g / m 2 .
[0138] The air-permeable member 2 can have the same properties as the porous film 1, such as air permeability in the thickness direction and / or water pressure resistance.
[0139] The air-permeable member 2 can be subjected to a liquid-repellent treatment and / or a coloring treatment.
[0140] The air-permeable member 2 can be used, for example, for a filter member. However, the use of the air-permeable member 2 is not limited to the above examples.
[0141] The shape of the air-permeable member 2 when viewed perpendicularly to the main surface of the air-permeable member 2 is, for example, a polygon including a square and a rectangle, a circle, an ellipse, or a band. The corners of the polygon can also be rounded. However, the shape of the air-permeable member 2 is not limited to the above examples. The band-shaped air-permeable member 2 can be wound to constitute a wound body. In addition, the winding can be performed in a state of being laminated with a release liner as necessary.
[0142] TheFigure 2 Example 2 of the deformation of the breathable component (wound body) is shown in Figure 4 . Figure 4 The coil 10 shown includes Figure 2 The ventilation member 2A and the release liner 11 are bonded together by an adhesive layer 12. In the winding body 10, the release surface 13 formed when the release liner 11 is peeled off from the ventilation member 2A is located between the ventilation member 2A and the adhesive layer 12. That is, in the winding body 10, when the release liner 11 is peeled off, the adhesive layer 12 is also peeled off from the ventilation member 2A, resulting in a ventilation member 2A without an adhesive layer 12 formed on its surface.
[0143] The breathable member 2A, supplied by the winding body 10 and without an adhesive layer 12 formed on its surface, can be joined to the opening of the housing by any joining method. That is, the joining method between the breathable member 2A and the opening of the housing has a high degree of freedom. Joining methods include, for example, joining based on a newly configured adhesive layer on the surface of the breathable member 2A, joining based on thermal fusion, and joining based on ultrasonic fusion.
[0144] The breathable member 2A supplied by the winding body 10 can be processed into any shape as needed. That is, the breathable member 2A has a high degree of freedom in shape. Here, "shape" includes "size". The above points mean that, according to the winding body 10, the breathable member 2A, which functions as a waterproof membrane, can be supplied in a state of high freedom in the method of engagement with the opening of the shell and / or in shape.
[0145] Furthermore, according to the winding body 10, the misalignment between the venting member 2A and the release liner 11 during winding is suppressed by the adhesive layer 12. In the winding body 10, the occurrence of faults (abnormal shape of the winding body) caused by winding tightness, etc., can be suppressed.
[0146] [Filter Components]
[0147] Figure 5 An example of the filter component of the present invention is shown. Figure 5 The filter member 4 (4A) includes the air-permeable member 2 described above, which is an air-permeable member having air permeability in the thickness direction and preventing foreign objects from passing through in that direction. The filter member 4A is disposed on, for example, the surface of an object having an opening, and prevents foreign objects from passing through the opening while ensuring air permeability through the opening. In this case, the filter member 4A is usually disposed such that the air-permeable member 2 covers the opening of the object.
[0148] The filter component 4A includes an adhesive layer 5 disposed on one side of the ventilating component 2. The ventilating component 2 is directly bonded to the adhesive layer 5. The filter component 4A can be disposed on the aforementioned surface of an object by means of the adhesive layer 5.
[0149] During the operation of the filter member 4 and during the arrangement to the object, a strong force is sometimes applied to the member 4 in a specific direction. However, the air permeable member 2 is provided with the porous membrane 1 having the tortoise shell-like structure formed of a plurality of nodes and a plurality of fibrils, and can suppress the reduction in the membrane thickness caused by compression. Therefore, for example, the filter member 4 can be manufactured without limiting the assembly direction of the air permeable member 2 (or the porous membrane 1) with respect to the filter member 4.
[0150] Examples of the adhesive constituting the adhesive layer 5 are an acrylic adhesive, a silicone adhesive, a urethane adhesive, an epoxy adhesive, and a rubber adhesive. In a case where the use of the filter member 4 under high temperature needs to be considered, an acrylic adhesive or a silicone adhesive having excellent heat resistance is preferably selected, and a silicone adhesive is particularly preferably selected. The adhesive layer 5 can be a double-coated adhesive tape without a substrate. The adhesive can also be a curable adhesive such as a phenol resin, an epoxy resin, a urea resin, a polyurethane resin, a melamine resin, and a polyester resin.
[0151] The outer periphery of the air permeable member 2 coincides with the outer periphery of the adhesive layer 5 when viewed perpendicularly to the main surface of the air permeable member 2. In addition, the shape of the adhesive layer 5 is a shape corresponding to the peripheral edge portion of the air permeable member 2 when viewed perpendicularly to the main surface of the air permeable member 2. The region of the air permeable member 2 to which the adhesive layer 5 is not joined can be used as the air permeable region of the filter member 4A. However, the shape of the adhesive layer 5 is not limited to the above-described example.
[0152] The area of the air permeable region is, for example, 40 mm 2 or more. The filter member 4 whose area of the air permeable region is in this range is, for example, suitable for arrangement to an object having an opening with a small diameter. The lower limit of the area of the air permeable region is, for example, 0.008 mm 2 or more. However, depending on the kind of the object to which the filter member 4 is arranged, the area of the air permeable region can also be a larger range.
[0153] Figure 6 A modification example 1 of the filter member 4 of Figure 5 is shown. Figure 6 The filter member 4 (4B) further has a substrate layer 6 arranged on one side of the air permeable member 2, and the air permeable member 2 and the adhesive layer 5 are joined via the substrate layer 6, and has the same configuration as the filter member 4A except for this. By the substrate layer 6, the strength and the operability of the filter member 4 can be improved, and the breakage of the air permeable member 2 during the operation or during the arrangement to the object can be suppressed.
[0154] Examples of the material constituting the base material layer 6 are polyolefins such as PE and PP, polyesters such as PET, silicone resins, polycarbonates, polyimides, polyamide-imides, polyphenylene sulfide, polyether ether ketone (PEEK), polyvinyl chloride, fluororesins, and metals such as aluminum and stainless steel. Examples of the fluororesin are PTFE, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), and tetrafluoroethylene-ethylene copolymer (ETFE). However, the material constituting the base material layer 6 is not limited to the above examples.
[0155] The outer periphery of the air permeable member 2 coincides with the outer periphery of the base material layer 6 when viewed perpendicularly to the main surface of the air permeable member 2. In addition, the shape of the base material layer 6 is a shape corresponding to the peripheral edge portion of the air permeable member 2 when viewed perpendicularly to the main surface of the air permeable member 2. The region of the air permeable member 2 where the base material layer 6 is not joined can be used as the air permeable region of the filter member 4B. However, the shape of the base material layer 6 is not limited to the above example.
[0156] The air permeable member 2 and the base material layer 6 can be joined by an adhesive or an adhesive agent, or can be joined by fusion such as heat fusion or ultrasonic fusion. The air permeable member 2 and the base material layer 6 can be joined by an adhesive layer. The adhesive layer can have the same constitution as the adhesive layer 5. The base material layer 6 and the adhesive layer 5 can be a base material and an adhesive layer of a single-sided adhesive tape or a double-sided adhesive tape, respectively.
[0157] Figure 7 A modification example 2 of the filter member 4 of Figure 5 is shown. Figure 7 The filter member 4 (4C) further has a base material layer 6 (6B) disposed on the other side of the air permeable member 2, and has the same constitution as the filter member 4B except for this. The air permeable member 2 is sandwiched by a pair of base material layers 6 (6A, 6B). By this sandwiching structure, the strength and the handleability of the filter member 4 can be further improved.
[0158] Figure 8 A modification example 3 of the filter member 4 of Figure 5 is shown. Figure 8The filter member 4 (4D) also has a tab film 7, and the base material layer 6 (6B) is joined to the tab film 7 by means of the adhesive layer 5 (5B), and has the same configuration as the filter member 4C except for this. The tab film 7 has a tab that protrudes outward of the outer periphery of the base material layer 6B when viewed perpendicularly to the main surface of the base material layer 6B. The filter member 4D can be handled by gripping the tab, and can be disposed to the surface of the object. The tab film 7 is normally removed when the filter member 4D is used. The tab film 7 can be made of the same material as the material that makes up the base material layer 6. Note that the tab film 7 is normally removed by gripping the tab and lifting it. At this time, a strong force is applied to the air permeable member 2 in the direction of lifting.
[0159] [member supply assembly]
[0160] The filter member 4 can be supplied, for example, by a member supply sheet. Figure 9 An example of a member supply assembly that is a supply method of the filter member 4 is shown. Figure 9 The member supply assembly 20 has a filter member 4 that is disposed to the surface of an object that has a surface with an opening, and a base material sheet 9 that has the filter member 4 disposed to the surface. Figure 9 The member supply assembly 20 shown in the drawing has a filter member 4D as the filter member 4.
[0161] The filter member 4 (4D) is disposed to the base material sheet 9 by means of the adhesive layer 5. According to the member supply assembly 20, the filter member 4 can be supplied efficiently to the process of being disposed to the surface of the object, for example.
[0162] The filter member 4 can also be disposed to the base material sheet 9 by means of an adhesive layer provided to the surface of the filter member 4 in the base material sheet 9. The adhesive layer of the surface is preferably weakly adhesive.
[0163] Although not shown in the drawing, a plurality of filter members 4 can be disposed to the surface of the base material sheet 9.
[0164] Examples of the material that makes up the base material sheet 9 are paper, metal, resin, and composite materials thereof. The metal is, for example, stainless steel and aluminum. The resin is, for example, polyester such as PET, and polyolefin such as PE and PP. However, the material that makes up the base material sheet 9 is not limited to the above examples. The base material sheet 9 can be in a single sheet shape, or in a tape shape. In the case where the base material sheet 9 is in a tape shape, the member supply assembly 20 can also be wound to form a roll.
[0165] Examples of objects to which the filter component 4 is disposed include the housing of electronic devices and the housing of electrical components for vehicles. The filter component 4 can be disposed on the outer surface and / or inner surface of the housing. In this case, the opening can also be a vent and / or a sound-transmitting opening provided in the housing. Examples of electronic devices include wearable devices such as smartwatches and wristbands; various cameras including action cameras and security cameras; information and communication devices such as mobile phones, smartphones and tablets; virtual reality (VR) devices; augmented reality (AR) devices; and sensor devices. Examples of electrical components for vehicles include vehicle lights and ECUs. However, the objects are not limited to the above examples.
[0166] The filter component 4 is configured to prevent foreign objects such as dust particles, water droplets, and other liquids from passing through.
[0167] Example
[0168] The present invention will now be described in more detail through examples. The present invention is not limited to the examples shown below.
[0169] [Example 1]
[0170] As the thermoplastic resin, poly(4-methylpentene-1) resin (manufactured by Mitsui Chemicals, RT18, melting point: 232°C) is prepared. As the plasticizer, a resin with a kinematic viscosity of 110 mmHg at 40°C is prepared. 2 / s of liquid paraffin (manufactured by MORESCO). Pentaerythritol tetra(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (manufactured by BASF Japan) was prepared as an antioxidant. 50.0 wt% of thermoplastic resin, 49.8 wt% of plasticizer, and 0.2 wt% of antioxidant were mixed to obtain a mixture. The mixture was kneaded using a LaboPlastomill (manufactured by Toyo Seiki Co., Ltd.) at 260°C for 30 minutes to obtain a homogeneous compound. The compound was hot-pressed using a compression molding machine heated to 260°C to obtain a pressed body. The pressed body was then contacted with water at 18°C while being held between a pair of polyimide plates, thereby cooling the pressed body to obtain a molded body.
[0171] Next, the molded body was subjected to simultaneous biaxial stretching using a biaxial stretching machine at a stretching temperature of 150°C and a stretching ratio of 2.5 times (longitudinal) × 2.5 times (transverse). The strain rate during stretching was 4% / s (2.6 mm / s) in both the longitudinal and transverse directions. This yielded a sheet. Finally, using methyl ethyl ketone (MEK) as the extraction solvent, the sheet was immersed in MEK at room temperature for 2 minutes for extraction. This removed the plasticizer from the sheet. To suppress sheet shrinkage, the extraction was performed while the sheet was fixed in a stainless steel frame. This yielded the porous membrane of Example 1.
[0172] Figure 10 Fig. 2 is a photograph (2500x) showing the results of observing the surface of the porous film of Example 1 with an SEM.
[0173] [Example 2]
[0174] As the plasticizer, liquid paraffin (manufactured by MORESCO Corporation) having a kinematic viscosity of 68 mm 2 / s at 40°C was prepared. The thermoplastic resin 70.0 wt%, the plasticizer 29.8 wt%, and the antioxidant 0.2 wt% were mixed to obtain a mixture. The mixture was kneaded using a Labo Plastomill under conditions of 230°C for 30 minutes to obtain a uniform kneaded product. Otherwise, the porous film of Example 2 was obtained by the same method as Example 1.
[0175] Figure 11 Fig. 4 is a photograph (2500x) showing the results of observing the surface of the porous film of Example 2 with an SEM.
[0176] [Example 3]
[0177] As the plasticizer, liquid paraffin (manufactured by MORESCO Corporation) having a kinematic viscosity of 92 mm 2 / s at 40°C was prepared. Otherwise, the porous film of Example 3 was obtained by the same method as Example 1.
[0178] Figure 12A Fig. 5 is a photograph (2500x) showing the results of observing the surface of the porous film of Example 3 with an SEM. Figure 12B is a partial enlarged view (10000x) of Figure 12A . Figure 12C Fig. 6 is a photograph (1500x) showing the results of observing the cross section of the porous film of Example 3 with an SEM.
[0179] [Example 4]
[0180] As the plasticizer, liquid paraffin (manufactured by MORESCO Corporation) having a kinematic viscosity of 68 mm 2 / s at 40°C was prepared. The thermoplastic resin 30.0 wt%, the plasticizer 69.8 wt%, and the antioxidant 0.2 wt% were mixed to obtain a mixture. The mixture was kneaded using a Labo Plastomill under conditions of 230°C for 30 minutes to obtain a uniform kneaded product. Simultaneous biaxial stretching was performed using a biaxial stretching machine under conditions of a stretching temperature of 150°C and a stretching ratio of 2.0 times (in the longitudinal direction) x 2.0 times (in the transverse direction). Otherwise, the porous film of Example 4 was obtained by the same method as Example 1.
[0181] Figure 13is a photograph (2500x) showing the result of observing the surface of the porous film of Example 5 with an SEM.
[0182] [Example 5]
[0183] Simultaneous biaxial stretching was performed using a biaxial stretching machine under conditions of a stretching temperature of 150°C and a stretching ratio of 2.0 times (in the longitudinal direction) x 2.0 times (in the transverse direction). Other than this, the porous film of Example 5 was obtained by the same method as in Example 1.
[0184] Figure 14A is a photograph (2500x) showing the result of observing the surface of the porous film of Example 5 with an SEM. Figure 14B is Figure 14A a partial enlarged view (10000x) thereof.
[0185] [Comparative Example 1]
[0186] As the thermoplastic resin, a poly(4-methylpentene-1) resin (manufactured by Mitsui Chemicals, Inc., MX002, melting point: 224°C) was prepared. As the plasticizer, a liquid paraffin (manufactured by MORESCO Corporation) having a kinematic viscosity of 68 mm 2 / s at 40°C was prepared. The thermoplastic resin 30.0 wt%, the plasticizer 69.8 wt%, and the antioxidant 0.2 wt% were mixed to obtain a mixture. The mixture was kneaded using a LaboPlastomill under conditions of 230°C for 30 minutes to obtain a uniform kneaded product. Other than this, the film of Comparative Example 1 was obtained by the same method as in Example 1.
[0187] Figure 15A is a photograph (2500x) showing the result of observing the surface of the film of Comparative Example 1 with an SEM. Figure 15B is Figure 15A a partial enlarged view (10000x) thereof. Figure 15C is a photograph (2000x) showing the result of observing the cross section of the film of Comparative Example 1 with an SEM.
[0188] [Comparative Example 2]
[0189] The thermoplastic resin 50.0 wt%, the plasticizer 49.8 wt%, and the antioxidant 0.2 wt% were mixed to obtain a mixture. Other than this, the film of Comparative Example 2 was obtained by the same method as in Comparative Example 1.
[0190] Figure 16 is a photograph (2500x) showing the result of observing the surface of the film of Comparative Example 2 with an SEM.
[0191] [Comparative Example 3]
[0192] A mixture was obtained by mixing the thermoplastic resin 70.0 wt%, the plasticizer 29.8 wt% and the antioxidant 0.2 wt%. Other than this, the film of Comparative Example 3 was obtained by the same method as Comparative Example 1.
[0193] Figure 17 is a graph (2500 times) showing the result of observing the surface of the film of Comparative Example 3 with an SEM.
[0194] The manufacturing conditions of Examples 1 to 5 and Comparative Examples 1 to 3 are shown in Table 1.
[0195] [Table 1]
[0196]
[0197] The porous films of Examples 1 to 5 and the films of Comparative Examples 1 to 3 were evaluated for the gas permeability, the water pressure resistance and the like by the above-described method of explaining the porous film. The evaluation results are shown in Table 2.
[0198] [Table 2]
[0199]
[0200] [Example 6]
[0201] The press body was cooled by contacting it with water at 90°C in a state of being sandwiched by polyimide plates, thereby obtaining a molded body. Other than this, the film of Example 6 was obtained by the same method as Example 1.
[0202] [Example 7]
[0203] The press body was cooled by contacting it with water at 5°C in a state of being sandwiched by polyimide plates, thereby obtaining a molded body. Other than this, the film of Example 7 was obtained by the same method as Example 1.
[0204] [Comparative Example 4]
[0205] The press body was cooled by standing it at room temperature, thereby obtaining a molded body. Other than this, the film of Comparative Example 4 was obtained by the same method as Example 1.
[0206] The manufacturing conditions of Examples 6 to 7 and Comparative Example 4 are shown together with the manufacturing conditions of Example 1 in Table 3. Figure 19 The results of measuring the actual temperature of the film from after heat-pressing until cooling with a thermocouple at intervals of 100 ms are shown for Example 1, Examples 6 to 7 and Comparative Example 4.
[0207] Figure 18A is a graph (2500 times) showing the result of observing the surface of the film of Comparative Example 4 with an SEM. Figure 18B is Figure 18AA close-up view (20000x) of the portion indicated by the arrow A in FIG. 1.
[0208] [Table 3]
[0209]
[0210] By Figures 10-12B and Figures 13-14B with Figures 15A-15B and Figures 16-17 As is apparent from a comparison between Examples 1 to 5 and Comparative Examples 1 to 3, the porous membranes of Examples 1 to 5 have a tortoise-shell-like structure formed of a plurality of nodes and a plurality of fibrils. Specifically, in the porous membranes of Examples 1 to 5, island-like regions formed of a plurality of nodes are irregularly connected, and these island-like regions are connected to each other by a plurality of fibrils. In contrast, the membranes of Comparative Examples 1 to 3 do not have such a tortoise-shell-like structure. In the membranes of Comparative Examples 1 to 3, since there are no island-like regions, the average interval between island-like regions and the average area of island-like regions cannot be calculated.
[0211] The porous membranes of Examples 1 to 5 contain a plurality of island-like regions and a plurality of fibrils extending in a plurality of directions from each island-like region. It is also confirmed that there are portions in which island-like regions are connected or overlap each other without the aid of a plurality of fibrils (see, for example, Figure 14B ). There are also porous membranes in which island-like regions and nodes as a plurality of nodes are mixed (see, for example, Figure 12B ). There are also porous membranes in which there are planar regions formed by a plurality of fibrils densely extending in a plurality of directions from each island-like region (see, for example, Figure 10 , Figure 11 ).
[0212] On the other hand, the membranes of Comparative Examples 1 to 3 exhibit a structure called a so-called unit structure that does not have clear nodes and fibrils.
[0213] As a reason why the tortoise-shell-like structure is formed in the porous membranes of Examples 1 to 5 and is not formed in the membranes of Comparative Examples 1 to 3, the following is presumed. The thermoplastic resin (RT18) used in Examples 1 to 5 and the thermoplastic resin (MX002) used in Comparative Examples 1 to 3 contain ethylene units as units of polymer chains. It is known that MX002 contains more ethylene units than RT18. Due to the difference in the content of ethylene units, the compatibility of the thermoplastic resin with the plasticizer and the temperature band at which the thermoplastic resin is precipitated as a solid phase differ between Examples 1 to 5 and Comparative Examples 1 to 3, and it is considered that these cause a difference in the structure after phase separation. It is considered that as a result, a tortoise-shell structure is finally obtained in Examples 1 to 5, whereas on the other hand, a unit structure that does not have a tortoise-shell structure is obtained in Comparative Examples 1 to 3.
[0214] In addition, in Examples 6 to 7 and Comparative Example 4 in which the same RT18 as that of Example 1 was used as the thermoplastic resin and the cooling conditions were changed, in Examples 6 to 7, the tortoise-shell structure was confirmed as in Example 1 (omitted illustration). On the other hand, in Comparative Example 4 in which air cooling was performed, the tortoise-shell structure could not be confirmed (refer to Figure 18A , Figure 18B ). As shown in Figure 19 , it is considered that in Comparative Example 4, since the cooling speed of the thermoplastic resin was relatively slow, the crystal growth and phase separation were greatly promoted, and the tortoise-shell structure was not formed. From this result, it is considered that the cooling conditions also affect the formation of the tortoise-shell structure.
[0215] Further, from the comparison between Figure 12C and Figure 15C , it is known that in the porous film of Example 3, a plurality of block-shaped nodes were uniformly present in the thickness direction. In contrast, in the film of Comparative Example 1, such a structure could not be confirmed.
[0216] As shown in Table 2, the porous films of Examples 1 to 5 had a thickness-direction compression rate Rc of 20% or less when a pressure of 2.5 N / mm 2 was applied. In contrast, the films of Comparative Examples 1 to 3 showed a compression rate Rc of 21.4% to 42.5%.
[0217] From these results, it is known that according to the porous films of Examples 1 to 5, the reduction in film thickness caused by compression at the time of mounting of a device to a housing or the like can be suppressed.
[0218] Industrial Applicability
[0219] The technology of the present application can be applied, for example, to a waterproof and breathable film, a waterproof and sound-transmitting film, a separator for an electricity storage device, and the like.
Claims
1. A porous film comprising a thermoplastic resin having a melting point of 180°C or higher and 300°C or lower as a main component, the porous film has a tortoise shell-like structure formed of a plurality of nodes and a plurality of fibrils.
2. The porous film according to claim 1, wherein a compression rate in a thickness direction of the porous film when a pressure of 2.5 N / mm 2 is applied is 20% or less.
3. A porous film comprising a thermoplastic resin having a melting point of 180°C or higher and 300°C or lower as a main component, The thickness direction compressibility of the porous film is 20% or less when a pressure of 2.5 N / mm is applied. 2 The thickness direction compressibility of the porous film is 20% or less when a pressure of 2.5 N / mm is applied.
4. The porous membrane according to any one of claims 1 to 3, wherein, the thermoplastic resin comprises a polymethylpentene resin.
5. The porous membrane according to any one of claims 1 to 3, wherein, When a cross section of the porous film is observed, a plurality of the nodes are contained along a thickness direction.
6. The porous film according to any one of claims 1 to 3, having a gas permeability of 1000 seconds / 100 mL or less in Gurley number.
7. The porous membrane according to any one of claims 1 to 3, wherein, The porous film has a porosity of 25% or more.
8. A filter member comprising: the porous film according to any one of claims 1 to 7; and an adhesive layer joined to the porous film.
9. A member supply assembly comprising: a filter member configured on a face of an object having an opening in the face; and a base material sheet having the filter member configured on a surface thereof, the filter member comprises: a porous film having a shape that covers the opening when configured on the face; and an adhesive layer joined to the porous film, the porous film is the porous film according to any one of claims 1 to 7.
Citation Information
Patent Citations
Olefin resin microporous biaxially oriented film, method for producing the same, heat-resistant olefin resin microporous biaxially oriented film, and method for producing the same
JP2017095576A
